All May Not Be Forgiven: Post Seminary Financial Liabilities for Diocesan Catholics Pursuing Ordination - Terkun, Kristina (Review of religious research, 2025)
Research on Catholic religious vocations has concentrated on student debt primarily as a barrier to entry. This study examines the outstanding liabilities for diocesan Catholics incurred post baccalaureate at the theologate level, shedding light on the misconception that seminarians do not accrue debt. Particular attention is given to the financial obligations of seminarians vis-à-vis their diocese while pursuing ordination and policies for settling debt if one discerns out of seminary or subsequently leaves the priesthood. A survey of Vocation Directors at dioceses that sponsor theologates in the United States was conducted and data collected via questionnaire. Responses analyzed from 21 dioceses across 14 states reveals remarkable consistency in financial policies. The vast majority are willing to accept men for theology with pre-existing educational debt. Further, dioceses cover most major expenses for seminarians in the theologate and nearly all consider there to be no debt incurred at the theologate level. Nevertheless, a common position among dioceses is that outstanding educational debt is primarily the seminarian?s responsibility. This study is relevant to candidates for the priesthood as well as diocesan leadership and acknowledges the role of donors or fundraisers in debt mitigation.